Are Wealthy Countries Always Healthy? Health Outcomes and Public Health Spending Nexus in Nigeria. (August 2021) - Orji, Anthony; Ogbuabor, Jonathan E.; Mba, Peter N.; Anthony-Orji, Onyinye I.
Nigeria is the most populous country in Africa and the eight most populous nation in the world. She is currently the largest economy in Africa. Nigeria is considered to be relatively wealthy in terms of oil reserves; however, the level of poverty is still very high because of corruption and mismanagement. This study investigates the impact of public health expenditure on health outcomes in Nigeria, 1985–2019. Empirical results from the Classical Regression Analysis reveal that health expenditure by the government reduces under-5 mortality rate significantly and improves life expectancy. Furthermore, immunization against measles was found to reduce under-5 mortality rate, while prevalence of HIV reduces life expectancy. The study therefore recommends that there is need for government expenditure on health to be targeted at areas that will improve health outcomes significantly. With adequate funding and proper monitoring, a resource-abundant nation like Nigeria, can become healthier. However, if this is not done, the wealthy may not be healthy after all.